FACTORS AFFECTING TAX AUDITOR INDEPENDENCE (Empirical Study of The Madya Tax Service Office of Malang) - Widyonanda Puspo Dewantoro (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study is to examine and analysis the factors affecting tax auditor independence. There are three examined factors examined which are individual factors, external factors, and organizational factors. Three factors are adopted from the regulation of The Audit Board of Republic Indonesia no. 01 year 2007 about the State Finance  Inspection Standards. Respondents  participated in this research are tax auditors working at Madya Tax Service Office of Malang. The number of respondents are 37 tax auditors. The respondent’s answers to the questions in the questionnaire used as data for this research. Then the data are presented in numbers so that the study can be categorized as quantitative research. Numerical data are processed using software SPSS 20 and the SPSS outputs help the researcher to analyze the results. The results show that individual factors, external, and organizational have an influence on tax auditor independence. The individual factors are the most dominant  factors affecting tax auditor independence. Thus, this study supports the regulation of The Audit Board of Republic Indonesia no. 01  year 2007 about the State Finance Inspection Standards. Keywords: Individual Factors, External Factors, Organizational Factors, Tax AuditorIndependence